Lymphangioma torsion of the omentum in a child: A case report - Johann Paulo S. Guzman, MD; Leandro L. Resurreccion, III, MD; Renato G. Bernaldez, MD; Marcus Lester R. Suntay, MD (Elsevier, 2017)
Lymphangiomas rarely present as intra-abdominal masses. These lymphatic malformations can arise in the mesentery, retroperitoneum and omentum. Omental cysts are usually benign and asymptomatic. We present an omental cyst with torsion in a pediatric patient presenting with abdominal pain and vomiting a few days before admission to our institution. Physical examination shows soft globular abdomen with a palpable tender mass in the mid abdomen. This patient was worked-up with an initial pre-op CT scan with IV contrast of the abdomen showing multiple intraabdominal cystic masses. Patient underwent laparotomy and complete excision of the omental cystic masses. Surgery mandates complete surgical excision to prevent recurrence. Patient was discharged without any untoward post-operative complications.